Multilocus sequence typing of Cryptococcus neoformans in non-HIV associated cryptococcosis in Nagasaki, Japan. (April 2013) - Mihara, Tomo; Izumikawa, Koichi; Kakeya, Hiroshi; Ngamskulrungroj, Popchai; Umeyama, Takashi; Takazono, Takahiro; Tashiro, Masato; Nakamura, Shigeki; Imamura, Yoshifumi; Miyazaki, Taiga; Ohno, Hideaki; Yamamoto, Yoshihiro; et al.
<x xml:space="preserve">Abstract</x> Cryptococcosis is primarily caused by two Cryptococcus species, i.e., Cryptococcus neoformans and C. gattii. Both include several genetically diverse subgroups that can be differentiated using various molecular strain typing methods. Since little is known about the molecular epidemiology of the C. neoformans/C. gattii species complex in Japan, we conducted a molecular epidemiological analysis of 35 C. neoformans isolates from non-HIV patients in Nagasaki, Japan and 10 environmental isolates from Thailand. All were analyzed using URA5-restriction fragment length polymorphism (RFLP) and multilocus sequence typing (MLST). Combined sequence data for all isolates were evaluated with the neighbor-joining method. All were found to be serotype A and mating type MATα. Thirty-two of the 35 clinical isolates molecular type VNI, while the three remaining isolates were VNII as determined through the URA5-RFLP method. Thirty-one of the VNI isolates were identified as MLST sequence type (ST) 5, the remaining one was ST 32 and the three VNII isolates were found to be ST 43. All the environmental isolates were identified as molecular type VNI (four MLST ST 5 and six ST 4). Our study shows that C. neoformans isolates in Nagasaki are genetically homogeneous, with most of the isolates being ST 5.